(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
An attractive smile has always been the focal point of a person’s attention to improve the aesthetic appearance and thus the self esteem. In a vast majority of growing, cooperative patients, the smile can be greatly improved with orthodontic treatment. The principles discussed in this paper will aid an orthodontist to systematically and consistently deliver high-quality, stable results with beautiful smiles. Frequent improvements in natural beauty can be observed once the ideal relationship between the denture and the facial soft tissues is restored. The different characteristics of smile can also help in identification of an individual. The present study was conducted on 50 male patients, aged 18-25 years, at the Pt. B.D. Sharma Post Graduate Institute of Medical Sciences, Rohtak. Photographs were taken using a high-resolution digital camera. The following parameters of smile were noted in all the subjects: number of teeth exposed during full smile, midline relationship of central incisors with philtrum and the bilateral negative space. The maximum number of teeth exposed during full smile was 10 in 44% of the cases, followed by 12-16 in 26% of the cases, 8 in 30% of the cases and 6 in 0% of the cases. The midline relationship of the central incisors with philtrum was central in 42% of the cases, followed by right of the centre in 42% of the cases and left of the centre in 16% of the cases, while the bilateral negative space was normal in 74% of the cases, followed by increased space in 26% of the cases. The present study provides the baseline data of an aesthetic smile in the Haryanvi males. The baseline data may serve as a guideline for the restoration or enhancement of aesthetics of the anterior component of the dentition.